Electroforming-Free and Multilevel Resistance Switching Properties in Al/TiOx/Cu Structure. (11th November 2014) - Zhou, Li W.; Shao, Xing L.; J. Chen, Chang; Jiang, Hao; Y. Wang, Jian; Chen, Ran; M. Zong, Qing; Zhao, Jin S.; R. Lv, Lian
Abstract : Multilevel resistance switching with electroforming behavior was studied in Al/TiOx /Cu structure. Electroforming-free was obtained through reducing the thickness of TiOx thin film, resulting in a relatively low reset current. Three stable resistance states were achieved from two step resets, indicating the multilevel resistance switching. Coexistence of conductive filaments of Cu and oxygen vacancies was proposed to explain multilevel resistance switching. The relationship among electroforming-free, low reset current and the concentration of Cu in TiOx was confirmed by Auger electron spectroscopy. A switching model for explaining electroforming-free and multilevel resistance switching properties was proposed.